PENGELOLAAN SAMPAH DI KOTA YOGYAKARTA: STUDI IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KOTA YOGYAKARTA - Petrus De Alanris Ohaq Lelangrian; Rumsari Hadi Sumarto (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
ABSTRACT Urban waste management has become one of the major challenges faced by the Government of Yogyakarta City, particularly following the enactment of Yogyakarta City Regional Regulation Number 9 of 2024 and the increasing pressure on the municipal waste management system after the closure of the Piyungan Regional Final Disposal Site (TPA Piyungan). These circumstances necessitate an evaluation of policy implementation to ensure the achievement of sustainable waste management objectives. This study aims to analyze the implementation of Yogyakarta City Regional Regulation Number 9 of 2024 based on Edward III’s four policy implementation variables: communication, resources, disposition, and bureaucratic structure. This research employed a qualitative descriptive approach using in-depth interviews, field observations, document analysis, and data analysis through the Miles and Huberman interactive model. The findings indicate that policy implementation has been carried out relatively well. Policy communication has been conducted hierarchically down to the neighborhood (RT) level; however, dissemination of the new regulation has not yet reached all community members. Resources are generally available, although limitations remain in land availability, operational facilities, and occupational safety equipment for field personnel. The disposition of implementers is reflected in the strong commitment demonstrated by the local government and field officers, while the bureaucratic structure exhibits effective inter-agency coordination. The novelty of this study lies in its comprehensive analysis of policy implementation based on Edward III’s four variables within the context of the implementation of Regional Regulation Number 9 of 2024 following the closure of the Piyungan Regional Final Disposal Site. The study concludes that although the policy has been implemented relatively effectively, its overall effectiveness can be further enhanced through broader policy dissemination, improved operational support, and strengthened collaboration among stakeholders to achieve sustainable urban waste management. ABSTRAK Pengelolaan sampah perkotaan menjadi salah satu tantangan utama yang dihadapi Pemerintah Kota Yogyakarta, terutama setelah diberlakukannya Peraturan Daerah Kota Yogyakarta Nomor 9 Tahun 2024 serta meningkatnya tekanan terhadap kapasitas sistem pengelolaan sampah pascapenutupan TPA Regional Piyungan. Kondisi tersebut menuntut evaluasi terhadap implementasi kebijakan agar tujuan pengelolaan sampah yang berkelanjutan dapat tercapai. Penelitian ini bertujuan menganalisis implementasi Peraturan Daerah Kota Yogyakarta Nomor 9 Tahun 2024 berdasarkan empat variabel implementasi kebijakan menurut Edward III, yaitu komunikasi, sumber daya, disposisi, dan struktur birokrasi. Penelitian menggunakan pendekatan descriptive qualitative melalui wawancara mendalam, observasi lapangan, dokumentasi, serta analisis data dengan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa implementasi kebijakan telah berjalan cukup baik. Komunikasi kebijakan dilaksanakan secara berjenjang hingga tingkat RT, meskipun sosialisasi regulasi terbaru belum menjangkau seluruh masyarakat. Sumber daya secara umum tersedia, namun masih dihadapkan pada keterbatasan lahan, armada operasional, dan perlindungan keselamatan kerja petugas. Disposisi pelaksana ditunjukkan melalui komitmen tinggi pemerintah daerah dan petugas lapangan, sedangkan struktur birokrasi memperlihatkan koordinasi lintas sektor yang berjalan efektif. Kebaruan penelitian ini terletak pada analisis implementasi kebijakan secara komprehensif berdasarkan empat variabel Edward III dalam konteks penerapan Peraturan Daerah Nomor 9 Tahun 2024 pascapenutupan TPA Regional Piyungan. Penelitian menyimpulkan bahwa efektivitas implementasi kebijakan masih memerlukan penguatan sosialisasi, peningkatan fasilitas operasional, serta optimalisasi kolaborasi antarpemangku kepentingan untuk mewujudkan pengelolaan sampah yang berkelanjutan.